Effect of vibrator application force on bone conduction out-put at different frequencies - MN, Vyasamurthy; T, Babu Punnan; B, Basu (Journal of All India Institute of Speech and Hearing)
Although the air-conduction pathway generally is considered to be the principal mode of sound transmission, the movements of a vibrating body may also be transmitted to the inner ear through direct contact with the skull’ . (Dirks, 1974)